Du projet d’accoucher « naturellement » à l’expérience de la césarienne en urgence - Ronald Guilloux (Anthropologie & Santé)
Based on a field survey of physiological birth plans carried out by women and midwives in a level 1 maternity unit in 2014, this article aims to understand the particular cases of three women who had a cesarean section (1 breech, 2 over-term), but with very different experiences: Catherine feels extreme frustration, Edwige relativises the event while Jade expresses immense joy. An analysis of the narratives by level of experience highlights several explanatory elements: their representations of “natural” childbirth and their expectations shaped over the course of their procreative itineraries, the ways in which they experience support from those around them, and their confrontation with the constraints of hospital operations. These elements may represent breaking points in the initial project and, depending on her procreative itinerary, each woman will be more or less able to rationalise this change retrospectively.